Impairment of Working Memory, Decision-making, and Executive Function in the First-Degree Relatives of People with Panic Disorder: A Pilot Study - Zhou, Zhenhe; Ni, Dongjie (Frontiers in Psychiatry, 2017)
Background Panic disorder (PD) patients present impairments of working memory, decision-making, and executive function. However, whether the first-degree relatives (FDRs) of people with PD present abnormal characteristics, including clinical and neuropsychological aspects, in comparison to the general population, has not been studied. Investigation and understanding of the abnormal neuropsychological characteristics of the FDRs of people with PD will contribute to the prevention and treatment of PD. Objective The purpose of this paper is to compare the working memory, decision-making, and executive function among people with PD, their FDRs, and controls. Materials and methods Neuropsychological functions of 30 people with PD, 30 FDRs of people with PD, and 30 controls were measured with a digit span task, Iowa Gambling Task (IGT), and Wisconsin Card Sorting Test (WCST). Results Perseverative errors, failure to maintain set scores, and number of cards chosen from decks A, B, C, and D were higher for People with PD and their FDRs than those of controls. Furthermore, error rates for these tests were higher for people with PD than their FDRs. Forward scores and backward scores, percentage of conceptual level responses, the number of categories completed, choices from advantageous minus disadvantageous decks, and mean amount of money earned of people with PD and their FDRs were all lower than those of controls. Scores for these tests were also lower for people with PD than for their FDRs. Conclusion People with PD as well as their FDRs present different degrees of impairments of working memory, decision-making, and executive function. Impaired performance on three tasks appears to be associated with the diathesis for PD and may be a valuable indicator of susceptibility for this disorder.